A rehabilitation gait for the balance of human and lower extremity exoskeleton system based on the transfer of gravity center. Issue 5 (19th August 2019) - Wang, Hansong; Yang, Canjun; Yang, Wei; Deng, Meiying; Ma, Zhangyi; Wei, Qianxiao
Abstract : Purpose: Most current lower extremity exoskeletons emphasize assistance for walking rather than stability. The purpose of this paper is to propose a rehabilitation gait based on the transfer of gravity center to improve the balance of exoskeleton rehabilitation training of the hemiplegic patients in the frontal plane, reducing the dependence on crutches/walking frames. Design/methodology/approach: The real-time and predictable instability factors of human and exoskeleton system (HES) are analyzed. Inspired by the walking balance strategy of the blind, a rehabilitation gait based on the transfer of gravity center is proposed and studied by modeling and experimental test and is finally applied to the prototype – Zhejiang University lower extremity exoskeleton (ZJULEEX) – to verify its feasibility. Findings: At least three real-time and predictable factors cause the instability of HES, and the factor of lateral tilt caused by gravity should be focused in the balance control of frontal plane. With the proposed gait, the hip height of stepping leg of HES does not reduce obviously even when the crutches do not work, which can improve the balance of HES. Research limitations/implications: However, the rehabilitation gait control needs to be more complete and intelligent to response to other types of perturbations to further improve the balance of HES. In addition, more clinical trials should be conducted to evaluate the effect of the proposed gait. Social implications: May bring happiness to the rehabilitation of patients with hemiplegia. Originality/value: The rehabilitation gait based on the transfer of gravity center to improve the balance of HES is first proposed and applied to HES.